Extracellular vesicles derived from pancreatic cancer cells BXPC3 or breast cancer cells MCF7 induce a permanent procoagulant shift to endothelial cells. Issue 187 (March 2020) - AmraneDjedidi, Rania; Rousseau, Aurélie; Larsen, Annette K.; Elalamy, Ismail; Van Dreden, Patrick; Gerotziafas, Grigoris T.
Abstract: The endothelium could be a potential target of cancer cell derived extracellular vesicles (CaCe-dEV). We investigated in vitro the effect of CaCe-dEV on the hemostatic balance of endothelial cells. Extracellular vesicles released from pancreas adenocarcinoma cells (BXPC3) or human breast cancer cells (MCF7) were isolated by differential centrifugation. Human umbilical vein endothelial cells (HUVEC) were cultured for 72 h in the presence or absence of CaCe-dEV. Subsequently, they were washed and re-cultivated over three cycles to get daughter cell generations (DG) which were not exposed to CaCe-dEV. Thrombin generation of normal platelet poor plasma (PPP) added in wells carrying HUVEC was assessed by the Calibrated Automated Thrombogram®. Tissue factor activity (TFa) and procoagulant phospholipid clotting time were assessed. Some traces of TFa were displayed by non-exposed HUVEC (0.18 ± 0.03 pM) and their EVs (1.2 ± 1.0 pM). Non-exposed HUVEC did not induce any detectable thrombin generation. BXPC3-dEV displayed significantly higher TFa as compared to MCF7-dEV (45 ± 5 pM versus 4.6 ± 2.3pM respectively; p  < 0.05). HUVEC exposed to CaCe-dEV enhanced thrombin generation. BXPC3-dEV induced significantly higher thrombin generation as compared to those exposed to MCF7-dEV. The procoagulant properties of HUVEC, acquired upon exposure to CaCe-dEV were transferred to DG. In conclusion, CaCe-dEV lead to a procoagulant shift of endothelial cells which, upon exposure, display TFa and enhance thrombin generation which is transferred to DG of HUVEC. The potency of CaCe-dEV to induce procoagulant shift of HUVEC depends on the histological type of the cancer cells. The procoagulant shift of endothelial cells which is transferable to DG could be an additional mechanism - together with cancer-induced blood hypercoagulability - in the pathogenesis of cancer associated thrombosis. Highlights: Endothelial cells exposed to CaCe-dEV acquire of procoagulant properties (TF expression and enhanced thrombin generation). The type of cancer cell from which CaCe-dEV stem determines the procoagulant transformation of endothelial cells. The procoagulant properties of endothelial cells exposed to CaCe-dEV are transferred to their daughter generations.